An unusual case of pediatric inflammatory multisystem syndrome, due to severe acute respiratory syndrome coronavirus-2 infection, presenting with complete heart block needing permanent pacing (Indian Journal of Case Reports, 2021)
Pediatric inflammatory multisystem syndrome due to severe acute respiratory syndrome coronavirus-2 infection is not very common. It may vary from a simple febrile inflammatory response to a severe multisystem involvement including myocarditis and shock. Here, we report the case of a 10-year-old female child with fever, rash, and mucositis who presented with shock and complete heart block along with encephalopathy and convulsions. The primary investigations revealed raised inflammatory markers along with a high titer of COVID antibodies. She was given full inotrope support along with immunomodulators. She underwent temporary pacing but ultimately needed a dual-chamber pacemaker. The novel coronavirus in children can present with a myriad of manifestations affecting almost every organ. In these pandemic times, one must always keep in mind the possibility of COVID-19 infection in a child that presents with shock, carditis, and arrhythmias. These children need intense immunosuppression and must be managed very aggressively